If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2 + 3x + -4 + 2x + 6 = 0 Reorder the terms: 2 + -4 + 6 + x + 3x + 2x = 0 Combine like terms: 2 + -4 = -2 -2 + 6 + x + 3x + 2x = 0 Combine like terms: -2 + 6 = 4 4 + x + 3x + 2x = 0 Combine like terms: x + 3x = 4x 4 + 4x + 2x = 0 Combine like terms: 4x + 2x = 6x 4 + 6x = 0 Solving 4 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 6x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 6x = 0 + -4 6x = 0 + -4 Combine like terms: 0 + -4 = -4 6x = -4 Divide each side by '6'. x = -0.6666666667 Simplifying x = -0.6666666667
| -2=b-150 | | 7+n=-8 | | 9.5-0.315x^2+0.743x=0 | | 2x-13=-81 | | 7-0.33333n=-28 | | 7-0.33333=-28 | | 46.5=3(4+5x) | | 2n+25=45 | | 48=5x+18 | | 2x-3+5(5x+2)= | | 10-3n=12 | | V-5/8=-1/4 | | 3n-10=12 | | f(x)=x^6/(2lnx) | | 32a^3-24a^2+36a=0 | | 1/x=-27/28 | | 80+13x=145 | | z/5-6=10/3 | | -7(v+2)=-4v-44 | | 3.53x+100=12.4609+10x | | -8h-8(2-4h)= | | 6(2n+3)=6(4n+5)+5 | | 7g-2(3g+1)-9= | | -w/-20=-2.5 | | 2x+16=3x^2 | | F(4)=-4+1 | | 3xy-y=2+5x | | -9/7x=3/4 | | 2.5(3p+5)=5p+12.5 | | 6(5u+1)-3(4u-12)= | | 4(2n+1)=7(3n+8)+2 | | 2b+b=450 |